Evaluation of web accessibility on Malaysia e-government web sites / Mohd Hanapi Abdul Latif - Abdul Latif, Mohd Hanapi (2006)
The advent of the WWW has caused a dramatic evolution in getting the information. From the web, most of the people nowadays can get information easily from Internet from anywhere and any time. These Web sites also become an important tool that the government used to market their institution to prospective customers and, to provide government information and services available on-line. To make these web sites more functional, they must be accessible to all users, including those with disabilities. This study tries to provide an overview of the accessibility of the selected Malaysia e-government Web sites. Nine Malaysia e-government Web sites were examined to find out how accessible they are with reference to the Web Content Accessibility Guidelines1.0 (WCAG) published by the World Wide Web Consortium (W3C). The evaluation of the Web sites had done using automatic validation tool, Bobby. This study also complemented with interview to the webmasters to gain better understanding of reasons that their sites are accessible or inaccessible. The research found that all the Malaysia e-government Web sites failed one or more WC3 web accessibility measures which mean disabled users may have substantial problems when accessing e-government websites. These accessibility problems have a relation with the awareness, skills and competencies of the webmaster regarding web accessibility. From the result, the knowledge of the webmaster on topic web accessibility is low. Several suggestions on how to improve the accessibility of Malaysia e-government websites are then offered.